2021
DOI: 10.1021/acsami.0c17154
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Titanium Nitride Nano-enabled Membranes with High Structural Stability for Efficient Photothermal Desalination

Abstract: Herein, we demonstrate the desalination performance of a solar-driven membrane distillation (MD) process, where upon light illumination, a highly localized heating of plasmonic titanium nitride nanoparticles (TiN NPs) immobilized on a hydrophobic membrane provides the thermal driving force for the MD operation. The engineered TiN photothermal membrane induces vapor generation directly at the feed–membrane interface upon solar irradiation, thereby eliminating the need to heat the entire bulk feed water. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Deshmukh et al [11] did a comprehensive study on nanoparticles, nanofluids, and their applications. Farid et al [12] The highest values of Von Mises stress and shear stress observed at all temperatures. Chan et al [14] examined the cocytoxity and antibacterial performance of TiN nanoparticles and laser nitrided titanium alloys.…”
Section: Introductionmentioning
confidence: 92%
“…Deshmukh et al [11] did a comprehensive study on nanoparticles, nanofluids, and their applications. Farid et al [12] The highest values of Von Mises stress and shear stress observed at all temperatures. Chan et al [14] examined the cocytoxity and antibacterial performance of TiN nanoparticles and laser nitrided titanium alloys.…”
Section: Introductionmentioning
confidence: 92%
“…In the wet state, the water layer on the membrane surface may reflect or absorb parts of the incident photons and reduce the number of effective photons reaching the membrane surface. 38,40 As a result, the temperature increases on the wet membrane surfaces were all relatively lower. In addition, the solar evaporation performances of asdeveloped membranes were tested using a laboratory device (Figure S4) under 1 kW m −2 simulated sunlight.…”
Section: Photothermal Conversion and Solar Evaporation Performancementioning
confidence: 99%
“…An advantage of this system is that the vapor can be condensed inside the module. In contrast, the main disadvantages came from the high conductive heat losses, which reduce the temperature difference across the membrane surface [ 90 , 91 , 92 ]. AGMD-based PMD: In this process, only the feed solution is in direct contact with the membrane surface, and an air gap is introduced between the membrane and condensing surface.…”
Section: Photothermal Membrane Distillationmentioning
confidence: 99%